1994
DOI: 10.1002/1097-0142(19940401)73:7<1882::aid-cncr2820730718>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 level in serum and ascites as a prognostic factor in patients with epithelial ovarian cancer

Abstract: Background. Interleukin‐6 (IL‐6) is a multifunctional cytokine that can be produced by human ovarian cancer cells. Elevated IL‐6 levels have been found in the serum and ascites of patients with ovarian cancer, but its role in this disease has not been clearly established. Methods. The authors studied the relationship between IL‐6 levels in serum and ascites, various tumor parameters, and survival in 70 patients with newly diagnosed, untreated epithelial ovarian cancer. Ascites and serum specimens were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 23 publications
4
88
2
1
Order By: Relevance
“…Inhibitory concentration 50% (IC 50 ) values were determined for each drug from a plot of log (drug concentration) versus percentage of cell growth inhibition. SDs were calculated on the basis of the IC 50 values obtained from at least 3 independent experiments.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…Inhibitory concentration 50% (IC 50 ) values were determined for each drug from a plot of log (drug concentration) versus percentage of cell growth inhibition. SDs were calculated on the basis of the IC 50 values obtained from at least 3 independent experiments.…”
Section: Growth Inhibition Assaymentioning
confidence: 99%
“…Clinically, individuals experiencing chronic stress have been shown to exhibit elevated circulating levels of IL-6 [51]. In ovarian cancer patients, elevated IL-6 is associated with poorer prognosis [52,53]. Lutgendorf and colleagues found that social support was associated with lower levels of IL-6 in the blood and ascites samples of ovarian cancer patients, thereby playing a protective role [54].…”
Section: Angiogenesismentioning
confidence: 99%
“…Among the cytokines reported to date, interleukin-6 (IL-6) is one of the pivotal immunoregulatory cytokines present in the ovarian cancer microenvironment; it induces several pathways leading to tumor proliferation, angiogenesis and chemoresistance (11). Higher serum and ascites levels of IL-6 have been found in patients with ovarian cancer than levels in patients with other malignancies, and levels have been shown to correlate with the extent of disease and poor clinical outcome (12)(13)(14). Tocilizumab is a humanized anti-human IL-6R antibody and binds to the IL-6-binding site of human IL-6R.…”
Section: Introductionmentioning
confidence: 99%